(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study investigated the relationship between digital expertise, stress-coping skills, and technological adaptability among secondary school teachers in the Division of Bukidnon. Utilizing a quantitative research design, 266 teachers participated in a survey that measured their levels of digital proficiency, coping strategies, and readiness to integrate technology into the classroom. Results consistently showed high levels of digital expertise and stress-coping skills, with teachers demonstrating confidence in using digital tools, in adopting adaptive teaching methods, and in engaging in continuous learning. Significant positive correlations were found between digital expertise and coping skills, on the one hand, and technological adaptability, on the other, indicating that teachers who possess strong technical competence and adaptive coping mechanisms are better equipped to manage technological change. Regression analysis revealed that adaptability and continuous learning, along with problem-focused coping, were the strongest predictors of technological adaptability. These findings underscore the importance of ongoing professional development, institutional support, and collaborative networks in maintaining teacher resilience and effectiveness in digitally enriched educational environments.